Asynchronous brain–computer interface for cognitive assessment in people with cerebral palsy. (5th October 2017) - Alcaide-Aguirre, R E; Warschausky, S A; Brown, D; Aref, A; Huggins, J E
Abstract: Objective . Typically, clinical measures of cognition require motor or speech responses. Thus, a significant percentage of people with disabilities are not able to complete standardized assessments. This situation could be resolved by employing a more accessible test administration method, such as a brain–computer interface (BCI). A BCI can circumvent motor and speech requirements by translating brain activity to identify a subject's response. By eliminating the need for motor or speech input, one could use a BCI to assess an individual who previously did not have access to clinical tests. Approach . We developed an asynchronous, event-related potential BCI-facilitated administration procedure for the peabody picture vocabulary test (PPVT-IV). We then tested our system in typically developing individuals ( N = 11), as well as people with cerebral palsy ( N = 19) to compare results to the standardized PPVT-IV format and administration. Main results . Standard scores on the BCI-facilitated PPVT-IV, and the standard PPVT-IV were highly correlated ( r = 0.95, p < 0.001), with a mean difference of 2.0 ± 6.4 points, which is within the standard error of the PPVT-IV. Significance . Thus, our BCI-facilitated PPVT-IV provided comparable results to the standard PPVT-IV, suggesting that populations for whom standardized cognitive tests are not accessible could benefit from our BCI-facilitated approach.